The relationships of man–space–nature–art: The pedagogy of experiences and art therapy as a source of educational inspiration - Godawa, Joanna (Studia Ecologiae et Bioethicae, 2019)
This article raises the issue of challenges in reshaping the educational system for sustainable development. It contains a description of the connections between human and nature. Its aim was to present the role of outdoor and ecological education in stimulating the development of children and adults. The author examines art therapy in the context of nature and ecology.